Visualization of morphological parenchymal changes in emphysema: comparison of different MRI sequences to 3D-HRCT - Ley-Zaporozhan, Julia; Ley, Sebastian; Eberhardt, Ralf; Kauczor, Hans-Ulrich; Heußel, Claus Peter (European journal of radiology, 2010)
Purpose - Thin-section CT is the modality of choice for morphological imaging the lung parenchyma, while proton-MRI might be used for functional assessment. However, the capability of MRI to visualize morphological parenchymal alterations in emphysema is undetermined. Thus, the aim of the study was to compare different MRI sequences with CT. - Materials and methods - 22 patients suffering from emphysema underwent thin-section MSCT serving as a reference. MRI (1.5T) was performed using three different sequences: T2-HASTE in coronal and axial orientation, T1-GRE (VIBE) in axial orientation before and after application of contrast media (ce). All datasets were evaluated by four chest radiologists in consensus for each sequence separately independent from CT. The severity of emphysema, leading type, bronchial wall thickening, fibrotic changes and nodules was analyzed visually on a lobar level. - Results - The sensitivity for correct categorization of emphysema severity was 44%, 48% and 41% and the leading type of emphysema was identical to CT in 68%, 55% and 60%, for T2-HASTE, T1-VIBE and T1-ce-VIBE respectively. A bronchial wall thickening was found in 43 lobes in CT and was correctly seen in MRI in 42%, 33% and 26%. Of those 74 lobes presented with fibrotic changes in CT were correctly identified by MRI in 39%, 35% and 58%. Small nodules were mostly underdiagnosed in MRI. - Conclusion - MRI matched the CT severity classification and leading type of emphysema in half of the cases. All sequences showed a similar diagnostic performance, however a combination of HASTE and ce-VIBE should be recommended.